Effect of body mass index on recurrence following urethroplasty - Rapp, David E.; Mills, James T.; Smith-Harrison, Luriel I.; Smith, Ryan P.; Costabile, Raymond A. (Translational Andrology and Urology; Vol 7, No 4 (August 15, 2018): Translational Andrology and Urology (Male Genitourinary Reconstruction and Trauma), 2018)
Background: Limited investigation exists to understand whether obesity affects outcomes of urethral reconstruction. We sought to assess whether body mass index (BMI) is an independent predictor for stricture recurrence following urethroplasty. Methods: We performed a retrospective review of patients undergoing urethroplasty between 2007–2014, identifying 137 patients for study inclusion. Data collected included BMI and patient demographic and surgical characteristics, including age, stricture length and location, etiology, and urethroplasty technique. Stricture-free survival analysis was performed using Kaplan-Meier method. Logistic regression was performed to assess predictors for stricture recurrence using both univariate and multivariate models. Results: Mean patient age and follow-up was 46.7 (±16.4) years and 91.8 (±30.5) months, respectively. A recurrence rate of 17% was identified, with a mean time to recurrence of 29 months. There was no difference when comparing the mean BMI in patients with and without recurrence (28.9 vs. 30.4 kg/m2, respectively) (P=0.4). A higher rate of stricture recurrence was seen when comparing the cohort with a BMI 30 kg/m2). However, in univariate and multivariate analysis, BMI failed to demonstrate statistical significance as a predictor for urethroplasty outcome. On multivariate analysis, fasciocutaneous repair type was predictive of stricture recurrence. No additional potential predictors assessed were found to be significant. Conclusions: In the present study, BMI did not independently predict for stricture recurrence following urethroplasty.